2020
DOI: 10.1101/2020.03.12.988725
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A regulatory interface on RIPK2 is required for XIAP binding and NOD signaling activity

Abstract: Signaling via the intracellular pathogen receptors Nucleotide-binding oligomerization domain-containing proteins NOD1 and NOD2 requires Receptor Interacting Kinase 2 (RIPK2), an adaptor kinase that can be targeted for the treatment of various inflammatory diseases. However, the molecular mechanisms of how RIPK2 contributes to NOD signaling are not completely understood. We generated FLAG-tagged RIPK2 knock-in mice using CRISPR/Cas9 technology to study NOD signaling mechanisms at the endogenous level. Using cel… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 68 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…Ubiquitylated RIPK2 serves as binding platform for TAK1/TAB1 complex which initiates inflammatory signalling ultimately leading to IL8 secretion (Hofer-Warbinek et al, 2000;Hasegawa et al, 2008;Heim et al, 2020). In order to examine the role of TAB1 and RIPK2 in XIAP-mediated IL8 secretion, we generated HCT116 cell lines (Varfolomeev & Vucic, 2008;Goncharov et al, 2018).…”
Section: Xiap Mediates Il8 Secretion In Melanoma By Involving Tab1 An...mentioning
confidence: 99%
See 1 more Smart Citation
“…Ubiquitylated RIPK2 serves as binding platform for TAK1/TAB1 complex which initiates inflammatory signalling ultimately leading to IL8 secretion (Hofer-Warbinek et al, 2000;Hasegawa et al, 2008;Heim et al, 2020). In order to examine the role of TAB1 and RIPK2 in XIAP-mediated IL8 secretion, we generated HCT116 cell lines (Varfolomeev & Vucic, 2008;Goncharov et al, 2018).…”
Section: Xiap Mediates Il8 Secretion In Melanoma By Involving Tab1 An...mentioning
confidence: 99%
“…Independently, XIAP has been long known to induce NFκB activation and MAP kinase signalling by involving TGFβ‐activated kinase 1 (TAK1) (Yamaguchi et al , 1999 ) upon direct interaction with the TAK1 binding protein (TAB1) via its BIR1 domain (Lu et al , 2007 ). Further studies showed that XIAP interacts via its BIR2 domain with the kinase domain of the receptor‐interacting protein kinase 2 (RIPK2), an adaptor of the NOD inflammatory signalling machinery (NFκB activation; Krieg et al , 2009 ; Heim et al , 2020 ). XIAP‐mediated NFκB activation was shown to involve its RING‐mediated ubiquitin ligase activity, characterising XIAP as an E3 ligase involved in cellular inflammatory signalling (Damgaard et al , 2012 ; Takeda et al , 2014 ).…”
Section: Introductionmentioning
confidence: 99%